A certificateless aggregate signature scheme for security and privacy protection in VANET. (May 2022) - Cahyadi, Eko Fajar; Su, Tzu-Wei; Yang, Chou-Chen; Hwang, Min-Shiang
In the vehicular ad hoc network, moving vehicles can keep communicating with each other by entering or leaving the network at any time to establish a new connection. However, since many users transmit a substantial number of messages, it may cause reception delays and affect the entire system. A certificateless aggregate signature scheme can provide a signature compression that keeps the verification cost low. Therefore, it is beneficial for environments constrained by time, bandwidth, and storage, such as vehicular ad hoc network. In recent years, several certificateless aggregate signature schemes have been proposed. Unfortunately, some of them still have some security and privacy issues under specific existing attacks. This article offers an authentication scheme that can improve security, privacy, and efficiency. First, we apply the certificateless aggregate signature method to prevent the onboard unit devices from leaking sensitive information when sending messages. The scheme is proven to be secure against the Type-1( A 1 ) and Type-2( A 2 ) adversaries in the random oracle model under the computational Diffie–Hellman problem assumption. Then, the performance evaluation demonstrates that our proposed scheme is more suitable for deployment in vehicular ad hoc network environments.